Mindfulness and Islamic parenting for adolescent mental health: A literature review - Leni Armayati; Iredho Fani Reza; Yanwar Arief; Maulin Annisa; Icha Herawati (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2025)
Adolescent mental health is a critical component of overall well-being and a key determinant of healthy development into adulthood. This period is marked by increased vulnerability to psychological stressors, particularly those arising from peer group dynamics. Parenting plays a pivotal role in shaping adolescent resilience and emotional regulation, especially when approached through mindful practices. Integrating mindfulness with Islamic values offers a holistic and culturally grounded parenting strategy that not only addresses emotional needs but also fosters spiritual and moral development. This study presents a literature review that systematically analyzed 11 journal articles and conference proceedings collected through the PICOT framework (Population, Intervention, Comparison, Outcome, Time) by accessing Google Scholar and the Garuda portal. The thematic synthesis revealed three main findings: (1) mindfulness contributes to improved emotional regulation and resilience among adolescents, (2) Islamic parenting values provide moral and spiritual grounding that strengthens coping strategies, and (3) the integration of mindfulness and Islamic parenting remains underexplored, particularly in relation to peer group dynamics in the digital era. These findings highlighted the potential of combining psychological mindfulness techniques with Islamic ethical values to promote emotional stability, self-regulation, and resilience among adolescents, while also underscoring the need for further empirical research to address gaps in the existing literature.